E-GOVERNMENT IN OPTIMIZING NON-TAX REVENUE OF THE MINING SECTOR IN INDONESIA - Rintis Nanda Pramugar; Reny Y. Sinaga (JAF (Journal of Accounting and Finance), 2021)
This research purpose to analyze the strategic and technical to encourage the potential of Regional Contribution of Non-Tax State Revenues (PNBP) of the mining sector is still not optimal in Indonesia given the existing number of inhibiting factors, such as corruption loophole, non-compliance, and inefficiency throughout the mining cycle. Whereas, several demands have raised by the community in mining governance, such as better government services, the need for flexibility and accuracy in formulating policies, and the need for improving the information technology of the PNBP management system. Based on the literature review using centralization and decentralization theory, two conclusions are produced. First, PNBP governance in the mining sector has not implemented e-government in integrating the central government, regional/local governments, Mining Business Permit holders, and competence stakeholders. Second, the e-government implementation should reflect public participation, transparency, and accountability at every stage of mining activities in overcoming the supervision weaknesses and the existing regulatory gaps that have caused the non-optimal of PNBP of the mining sector.